The Role of Artificial Intelligence in Enhancing the Effectiveness and Efficiency in Audit Firms - Hady, Aufar Fadlul; Fitria, Maulidah (STAI Nurul Islam Mojokerto, 2025)
This research explores how Artificial Intelligence (AI) can revolutionize audit practices by investigating how AI can be implemented in audit firms and the resulting impact on those practices. The research design utilizes a qualitative case study approach, which provides in-depth insight into the adoption of AI within audit firms. By examining the perspectives of auditors, managers, and other stakeholders, this research highlights the factors that influence AI implementation. The research findings reveal that AI offers powerful tools for audit firms, namely automating repetitive tasks, analyzing massive data sets to detect risks, and improving communication and collaboration. These advancements could result in greater efficiency, potentially better audit quality, and more streamlined workflows. However, challenges remain. Auditors may exhibit biases toward human specialists, and data quality is critical to successful AI integration. Overall, this research contributes valuable knowledge to both academic literature and practical applications in auditing.